PROFIT AND LOSSES OF BOYCOTTING UNILEVER PRODUCTS (PANCASILA ECONOMIC AND MASLAHAH PERSPECTIVE) - Lestari Wuryanti; Euis Mufahamah; Wuri Astamala Dewi; Arie Fitria; Kalijunjung Hasibuan (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The boycott policy against Unilever products is seen as a form of firm legal standing on which the Indonesian people stand and aims to provide a deterrent effect against any party that supports Israel's attack on Pakistan. Therefore, this research aims to analyze these policies from the perspective of Pancasila Economics and Maslahah Al-'Ammah. This research is qualitative research with an explanatory approach. The data used in this research is secondary data that researchers obtained from scientific articles, books, magazines, credible websites, and a number of other sources that are usually used in every research. The research results show that first, The boycott policy against Unilever products has a number of strengths and opportunities as indicators of profits and a number of weaknesses and threats as indicators of equal losses. However, a number of weaknesses and threats lie in materialistic matters such as loss of salaries for employees, loss of jobs, increased unemployment, and so on. A number of strengths and opportunities as indicators of profit lie in principal matters that are in line with the philosophy of Panacasila and Maslahah Al-A'mmah including humanity, justice, welfare and equality. Second, The policy of boycotting Unilever products is in line with the principles of Pancasila economics which do not only view profits as materialistic in nature, but profits must also uphold human, divine, justice and welfare values. Last, The boycott policy of Unilever products is in line with the concept of Maslahah Al-'Ammah which upholds human values, namely that dharuriyyah needs must be fulfilled in every human being in general and the Palestinian community in particular. Thus, anything that prevents the fulfillment of these needs must be opposed at all costs. One way is to boycott Unilever products. Keywords: Boycotting, Unilever, Pancasila Economic, Maslahah Perspective